2020
DOI: 10.1093/ehjqcco/qcaa018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on outcomes in elderly patients with acute myocardial infarction who undergo percutaneous coronary intervention

Abstract: Aims  Frailty is characterized by reduced biological reserves and weakened resistance to stressors, and is common in older adults. This study evaluated the prognostic implications of frailty at hospitalization in elderly patients with acute myocardial infarction (AMI) who undergo percutaneous coronary intervention (PCI). Methods and results  We prospectively analysed 546 AMI patients aged ≥80 years undergoing PCI from 2009 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…As evaluation of frailty based on conventional definitions such as gait speed and grip strength 5,15 are difficult during the acute phase of AMI because of safety concerns, we used a novel, simple definition of frailty created based on the Canadian Study on Health and Aging that includes measures of functional and cognitive performance in categorising the degree of frailty. 8,9,17 Our results suggest that additional treatments are needed to prevent progression of frailty as well as all-cause mortality in this population.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…As evaluation of frailty based on conventional definitions such as gait speed and grip strength 5,15 are difficult during the acute phase of AMI because of safety concerns, we used a novel, simple definition of frailty created based on the Canadian Study on Health and Aging that includes measures of functional and cognitive performance in categorising the degree of frailty. 8,9,17 Our results suggest that additional treatments are needed to prevent progression of frailty as well as all-cause mortality in this population.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, we and other investigators have shown that frailty status is associated with inhospital and mid-term mortality in patients with acute coronary syndrome. 9,15,16 However, there have been few reports about changes in frailty status, which we addressed in this study. This study demonstrated that more than 40% of nonagenarians with AMI undergoing PCI were frail at admission and the proportion of patients with frailty clearly increased during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, risk stratification for its prevention should be carried out in the early phase [ 2 , 3 , 4 , 5 ]. Previous reports have suggested a number of possible predictors of cardiovascular events after AMI, including patient background, electrocardiographic features, factors of reperfusion therapy including onset-to-balloon time, ventricular dysfunction, frailty, and poor nutritional status [ 6 , 7 , 8 ]. Serum albumin is one of the most important nutritional indicators.…”
Section: Introductionmentioning
confidence: 99%